Design and calculation of the connection reinforcing bars crimping sleeves - Luchko, Y. Y.; Pentsak, A. Ya.; Pelekh, R. Ya. (Science and Transport Progress, 2008)
The problem of connection of high-strength carbon and thermomechanically strengthened reinforcements is considered in the paper. The analysis of results of previous investigations from world practice is conducted. The construction of connection is offered and the research of the beam reinforced concrete elements reinforced by the combined reinforcement on durability, crack-durability and deformations is conducted. This research showed the expedience of such a connection and reliable working capacity of the reinforced concrete constructions reinforced by the combined reinforcement.